임농복합경영 대상지 적지 분석: 북한 황해북도 수안군을 중심으로 - 권수경; Sookyung Kwon; 박소영; Soyoung Park; 권순덕; Soonduck (한국산림과학회지, 2022)
혼농임업(agroforestry)은 임업, 농업, 축산업을 병행하여 지속적인 농업을 가능케 하는 생태·경제적 토지이용 체계로, 임농복합경영은 혼농임업의 북한식 표현이다. 북한은 경사 산지 및 산림황폐지 복구를 위한 전략으로 임농복합경영을 선택하였다. 임농복합경영은 남북산림협력 분과회담의 의제로 제시된 바 있으며, 한반도 산림탄소흡수원을 확충하고 ‘2050 탄소중립 전략’과 ‘한반도 그린데탕트’를 추진하기 위한 수단으로 주목받고 있다. 본 연구는 북한 산림황폐지 상시 모니터링 지역이자 ICRAF(세계혼농임업센터) 혼합임농경영 시범지인 황해북도 수안군을 대상으로 하여 임농복합경영 대상지 적지 분석을 수행하였다. 문헌 분석을 통해 임농복합경영 대상지 입지조건을 분석하여 대상지 선정의 기준을 정하고, GIS 중첩분석을 응용하여 임농복합경영 적지 분석 지도를 제작하여 시각화하였다. 약 8,839 ha의 경사지가 임농복합경영에 적합한 지역으로 선정되었으며, 이는 수안군 전체 면적의 약 15%에 해당하였다. 본 연구에서 제작한 지도와 구글 어스 위성영상을 대조하여 육안판독을 통해 수안군의 임농복합경영 등 토지이용 현황을 확인하고 결과를 검증하였다. 본 연구는 향후 자연환경적인자와 사회경제적인자에 대한 고찰을 통해 인자 간 상대적 중요도를 평가하고, 전국적 단위에서 정확도 높은 임농복합경영 적지 분석 지도를 제작하여 남북산림협력 정책의 기초자료를 제작하는데 기여할 것이다. Agroforestry is an ecological and economic land-use system that enables sustainable agriculture by combining forestry, agriculture, and livestock industries. North Korea chose agroforestry as a strategy for the restoration of sloping land and deforested land. Agroforestry was proposed for the inter-Korean forest cooperation subcommittee meeting and is currently highlighting carbon removal and promoting the ‘2050 Carbon Neutral Strategy’ and ‘Korea Peninsula Green Detente.’ The study area, Suan-gun, Hwanghaebuk-do, is a constant deforestation monitoring area and a pilot site for management by the International Center for Research in Agroforestry. The requirements for agroforestry were analyzed through literature analysis. The agroforestry site-suitability map was visualized by applying GIS overlap analysis. Approximately 8,839 ha of sloping area was selected as suitable for agroforestry management, which is about 15% of Suan. We compared the map with Google Earth images and visually detected the land use status, such as agroforestry in Suan, to verify the results. As a future study, we will consider both natural-environment and socioeconomic factors and evaluate the relative importance of the factors to produce a high-accuracy agroforestry sitesuitability map at the national scale with the goal of producing basic data for the inter-Korea forest cooperation policy for long-term goals.